Collection development in Tawang monastery libraries. Issue 2 (3rd April 2017) - Laloo, Bikika; Sumnyan, Chaphun
Abstract : Purpose: Monastery libraries have, for centuries, been the hub of religious education and research. They house collections that are unique and even rare and have been useful to students of religion as well as to members of the public. Some, along with the monasteries to which they are attached, even serve as tourist attractions, being as they are ancient relics with rich culture and history. The Tawang Monastery, in Arunachal Pradesh, India, is one such monastery whose libraries are unique and valuable. This paper reports results of a study on the collection in the two libraries of Tawang Monastery which not only found that they are among the best in terms of format, variety and value but also discovered shortcomings like shortage in staff and space which need to be addressed at the earliest. Design/methodology/approach: For this research, case study method was used by the researchers. The tools used for data collection were questionnaire and interview. This is because they were found to be easier and convenient methods to carry out this research. Apart from that, observation method was also carried out throughout the research period. Besides these field work research methods, literature review was also carried out to gather mostly historical and some background information about the monastic libraries in India. Internet searching was also carried out to find out other relevant information. Findings: This study provides an enumerative account of collection development in the Tawang monastery libraries. During the study, certain pitfalls were noted. First, the ancient Parkhang library building is in a very precarious state of existence. In fact, the library building was undergoing renovation during the period of this study. Due to this very reason also, it's collection of Kanjur and Tanjur religious texts have not been subjected to any preservation methods, although it is of utmost necessity. Research limitations/implications: During this particular period of study the ancient Parkhang library was undergoing the process of building renovation. In fact, the whole library building was deserted as a result, and was in topsy-turvy condition. The tour of the library hall was given, for whatever it was worth by the librarian himself, during which some photographs were taken. Hence, most of the data collection was possible only due to the dedicated cooperation of the monks and a few learned teaching staff of the monastery school. Much relevant information was collected through personal interviews, apart from the questionnaire sets. On the other hand, no such hindrance was faced for the data collection from the school library. Originality/value: This study, to an extent, shows that the collection development in the Tawang monastery libraries (especially Parkhang library) is a very vital and important asset, both for the state of Arunachal Pradesh and for India as well. It is the first full-fledged study on collection development in the Tawang Monastery libraries, covering all aspects of the topic at hand, and can serve as a precedent to other such studies.